Enhancing feedback and improving feedback: subjective perceptions, psychological consequences, behavioral outcomes. Issue 12 (12th September 2016) - Sedikides, Constantine; Luke, Michelle A.; Hepper, Erica G.
Abstract: Three experiments examined subjective perceptions, psychological consequences, and behavioral outcomes of enhancing versus improving feedback. Across experiments, feedback delivery and assessment were sequential (i.e., at each testing juncture) or cumulative (i.e., at the end of the testing session). Although enhancing feedback was seen as more satisfying than useful, and improving feedback was not seen as more useful than satisfying, perceptions differed as a function of short‐term versus long‐term feedback delivery and assessment. Overall, however, enhancing feedback was more impactful psychologically and behaviorally. Enhancing feedback engendered greater success consistency, overall satisfaction and usefulness, optimism, state self‐esteem, perceived ability, and test persistence intentions; improving feedback, on the other hand, engendered greater state improvement. The findings provide fodder for theory development and applications.